2015
DOI: 10.2174/1566523215666150126122317
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Improvement, Increased Life-Span and Sustained Cell Homing in Amyotrophic Lateral Sclerosis After Transplantation of Human Umbilical Cord Blood Cells Genetically Modified with Adeno-Viral Vectors Expressing a Neuro-Protective Factor and a Neural Cell Adhesion Molecule

Abstract: Amyotrophic lateral sclerosis (ALS) is an incurable, chronic, fatal neuro-degenerative disease characterized by progressive loss of moto-neurons and paralysis of skeletal muscles. Reactivating dysfunctional areas is under earnest investigation utilizing various approaches. Here we present an innovative gene-cell construct aimed at reviving inert structure and function. Human umbilical cord blood cells (hUCBCs) transduced with adeno-viral vectors encoding human VEGF, GDNF and/or NCAM genes were transplanted int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 26 publications
0
34
0
1
Order By: Relevance
“…Evidence for grafted cells in the endothelium of capillaries has been shown previously [26], but the data did not indicate that these cells had transmigrated through the vessel wall and differentiated into endothelial cells. Our data indicates differentiation of progenitors in hUCB-MC population into endothelial cells.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Evidence for grafted cells in the endothelium of capillaries has been shown previously [26], but the data did not indicate that these cells had transmigrated through the vessel wall and differentiated into endothelial cells. Our data indicates differentiation of progenitors in hUCB-MC population into endothelial cells.…”
Section: Discussionmentioning
confidence: 66%
“…For these cells, alternative pathways of differentiation could include formation of microglial cells or macrophages. Previously our group reported that hUCB-MCs may differentiate into microglia-like (Iba1 + ) cells in spinal cord after transplantation in ALS mice [26]. Elucidation of the differentiation pathways requires further studies including immunocytochemical typing.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] In previous studies on amyotrophic lateral sclerosis treatment, we developed UCB-MCs transfected with a pBudCE4.1 dual-expression-cassette plasmid vector encoding vascular endothelial growth factor and cell adhesion molecule (VEGF-L1CAM) and VEGF-FGF2 19,20 and UCB-MCs transduced concurrently with adenoviral vectors encoding VEGF and GDNF, VEGF and neural cell adhesion molecule (NCAM), or GDNF and NCAM. 21 The main positive action of the UCB-MCs was that they facilitated targeted delivery of the recombinant therapeutic molecules to motor neurons and thereby prolonged the survival of the neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Заготовку крови пуповины про-изводили по инструкции банка стволовых клеток Казанского государственного меди-цинского университета. Выделение МККП проводили в градиенте плотности фиколла по стандартной методике [6].…”
Section: экспериментальная медицинаunclassified